1999
DOI: 10.1002/(sici)1096-8628(19990528)84:3<300::aid-ajmg27>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Premature ovarian failure (POF) and fragile X premutation females: From POF to fragile X carrier identification, from fragile X carrier diagnosis to POF association data

Abstract: Early menopause in the fragile X carriers has been well documented in several reports. All surveys demonstrated that 13-25% of fragile X carriers experienced premature ovarian failure (POF), defined as menopause before the age of 40 years. In 1995 we started screening two groups of subjects as a part of a Fragile X Research Program: 1) women previously diagnosed as fragile X carriers from the register of our center and 2) women with POF and without a family history of fragile X or other forms of mental retarda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…In addition, pre-mutation carriers are at risk of developing fragile X-associated primary ovarian insufficiency (FXPOI) and fragile X-associated tremor/ataxia syndrome (FXTAS) in late adult life, although they are mentally normal. 5,6 Intermediate alleles are repeat numbers between 45 and 54, and individuals carrying theses alleles are at risk of expanding into pre-mutation but not into full mutation. [7][8][9] Because of the significant morbidity associated with FXS, and since most maternal carriers are clinically silent during their reproductive years, many experts have put forward the notion of preconception or prenatal fragile X carrier screening for females.…”
Section: 採用強力Fmr1基因聚合酶連鎖反應法偵測華籍 婦女的X染色體脆折症準突變帶因者:篩查和 產前診斷的意義mentioning
confidence: 99%
“…In addition, pre-mutation carriers are at risk of developing fragile X-associated primary ovarian insufficiency (FXPOI) and fragile X-associated tremor/ataxia syndrome (FXTAS) in late adult life, although they are mentally normal. 5,6 Intermediate alleles are repeat numbers between 45 and 54, and individuals carrying theses alleles are at risk of expanding into pre-mutation but not into full mutation. [7][8][9] Because of the significant morbidity associated with FXS, and since most maternal carriers are clinically silent during their reproductive years, many experts have put forward the notion of preconception or prenatal fragile X carrier screening for females.…”
Section: 採用強力Fmr1基因聚合酶連鎖反應法偵測華籍 婦女的X染色體脆折症準突變帶因者:篩查和 產前診斷的意義mentioning
confidence: 99%
“…Ishizuka frequency of FMR1 premutations among Japanese patients with POI. The frequency of premutation carriers among women with the sporadic form of POI ranges between 1.6% and 3.3% (27,(28)(29)(30)(31) in Caucasian populations, and one study has described a frequency of 4.8% in a group of screened Slovenian patients (32). A study of 80 Indian patients with POI revealed that none of them had CGG repeats within the premutation range (33).…”
Section: Figurementioning
confidence: 99%
“…Women with premutation level repeats in this gene are at increased risk of premature ovarian failure, [1][2][3] alternatively termed primary ovarian insufficiency. Some reports have suggested that women with 35 to 44 CGGs, 4,5 35 to 54 CGGs, 6 and <28 CGG repeat lengths 7 may be associated with less severe ovarian dysfunction, often manifest as diminished ovarian reserve.…”
Section: Introductionmentioning
confidence: 99%